2022
DOI: 10.3389/fnut.2022.937959
|View full text |Cite
|
Sign up to set email alerts
|

Organic Egg Consumption: A Systematic Review of Aspects Related to Human Health

Abstract: Consumption of organic foods has increased recently, but evidence about their potential health benefits is still limited. This systematic review aims to synthesize the available scientific evidence on the association between organic egg consumption and human health. We searched for peer-reviewed articles on this subject indexed in the MEDLINE, EMBASE, Web of Science and Cochrane Library databases from the inception date to April 13, 2022. This review was based on PRISMA guideline recommendations. Three studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Evidence for the relationship between egg consumption and human health is controversial, with some studies finding a reduction in the risk of hemorrhagic stroke and levels of inflammatory factors, but no association in others (e.g., cancer, CVD, etc.) ( 8 , 9 ). Eggs were found to be negatively associated with MetS in a prospective study in Korea and a cross-sectional study in China ( 7 , 10 ), while a positive association was found in an Iranian cohort ( 11 ), and no significant association was found in an Australian and another Korean cohort ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the relationship between egg consumption and human health is controversial, with some studies finding a reduction in the risk of hemorrhagic stroke and levels of inflammatory factors, but no association in others (e.g., cancer, CVD, etc.) ( 8 , 9 ). Eggs were found to be negatively associated with MetS in a prospective study in Korea and a cross-sectional study in China ( 7 , 10 ), while a positive association was found in an Iranian cohort ( 11 ), and no significant association was found in an Australian and another Korean cohort ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%